The community and dynamic dictionary as a lever for strengthening ethnolinguistic identity - Stephen A., Marlett (2004)
In this article, it is argued that the linguistic importance of the dictionary is greatly increased if it is the result of the work of the entire community (what can be called a community dictionary). The elaboration of such an important document should not be done in isolation, turning its back on the community. It is better for the community to become deeply involved, with the advice of lexicography experts, in the elaboration of the dictionary of its language. In this way, they have a powerful tool to reaffirm their identity and achieve the revaluation of the language in question. The following ideas are based on lexicographic work with a view to creating a dictionary of the Seri language.